After modern art : 1945-2017 - Hopkins, David, 1955- (Oxford : Oxford University Press, 2018)
"A beautifully illustrated, new edition of this pioneering study of art since 1945. Focussing mainly on the relationship between American and European Art, this book offers an up-to-date introduction to the major artists and movements of recent years."--
First published in 2000 as: After modern art : 1945-2000.
Final chapter covers 21st century art.
Includes bibliographical references (pages 275-294) and index.
Keywords: 1900-2099; Art, American -- 20th century; Art, European -- 20th century; Art, American -- 21st century; Art, European -- 21st century; Art, American; Art, European